"You can Run, but You Cannot Hide!" Mapping Journalists' Experiences With Hostility in Personal, Organizational, and Professional Domains. (June 2023) - Ivask, Signe; Lon, Angelina
Our study describes how hostility reaches journalists and their reactions to the experiences. Semi-structured interviews with 18 Estonian journalists were conducted in 2021 from June to December. We divided journalists' experiences into personal, professional, and organizational domains. One key observation is that journalists cannot avoid work-related hostility, even when off-duty. In addition, as one journalist receives hostility in a myriad of ways, there is a necessity for a multilevel approach when teaching about coping with or preventing unnecessary hostility from reaching journalists. Our mapping can be used when preparing students for occupational hazards or developing journalism curricula.